PENANGGULANGAN TINDAK PIDANA MAIN SENDIRI OLEH MASYARAKAT (Studi Penelitian pada Kepolisian Sektor Babussalam Kabupaten Aceh Tenggara) - Riska Sintania SKD; Husni H; Teuku Yudi Afrizal (Fakultas Hukum Universitas Malikussaleh, 2022)
Judgment itself is an arbitrary act against people who are considered guilty. This is contrary to Article 170 of the Criminal Code paragraph (1) which reads